Green Strength Optimization of Injection Molding Process for Novel Recycle Binder System Using Taguchi Method - Ibrahim, Mohd Halim Irwan; Kamarudin, Nurhafizah (International Journal of Integrated Engineering, 2020)
Metal injection molding is a worldwide technology that world use as a predominant method in manufacturing. Optimizing the injection molding process is critical in obtaining a good shape retention of green components and improving manufacturing processes itself. This research focuses on the injection molding optimization which correlated to a single response of green strength which implementing orthogonal array of Taguchi L9 (34). It involved the effect of four molding factors: injection temperature, mold temperature, injection pressure and injection speed, towards green strength. The significant levels and contribution to the variables of green strength are determined using the analysis of variance. Manual screening test is conducted in regards of identifying the appropriate level of each factors. The study demonstrated that injection temperature was the most influential factor contributes to the best green strength, followed by mold temperature, injection speed and injection pressure. The optimum condition for attaining optimal green strength was definitely by conducting injection molding at; 160 ÂºC of injection temperature, 40 ÂºC of mold temperature, 50 % of injection pressure and 50 % of injection speed. The confirmation experiment result is 15.5127 dB and it was exceeding minimum requirement of the optimum performance. This research reveals that the proposed approach can excellently solve the problem with minimal number of trials, without sacrificing the ability of evaluating the appropriate condition to achieve related response, which is green strength.